2014
DOI: 10.1080/10439463.2013.875015
|View full text |Cite
|
Sign up to set email alerts
|

Proactive policing and equal treatment of ethnic-minority youths

Abstract: Proactive policing aims at suppressing delinquency at an early stage. In the Netherlands, it is applied, inter alia, to youths and youth groups to prevent them from slipping off into delinquent behaviour and crime. Proactive policing implies that police officers keep in touch with local youths and monitor their behaviour. Furthermore, it entails police officers applying discretion in giving warnings, in asking for identification and in conducting stop and search. This contribution reports on an empirical inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…Recently there has been a heated discussion on the issue of ethnic profiling by the Dutch police. The results of empirical research are not conclusive so far (Bovenkerk, 2014;Cankaya, 2012;Svensson and Saharso, 2014). However, as Junger-Tas argued about the exceptional rise of Moroccan crime rates that began to appear in the 1990s: 'Even if the police is prejudiced this would not explain the disparities in crime rates between various minorities.…”
Section: Introductionmentioning
confidence: 97%
“…Recently there has been a heated discussion on the issue of ethnic profiling by the Dutch police. The results of empirical research are not conclusive so far (Bovenkerk, 2014;Cankaya, 2012;Svensson and Saharso, 2014). However, as Junger-Tas argued about the exceptional rise of Moroccan crime rates that began to appear in the 1990s: 'Even if the police is prejudiced this would not explain the disparities in crime rates between various minorities.…”
Section: Introductionmentioning
confidence: 97%
“…Especially youngsters with a Moroccan background are seen as disproportionally involved in various forms of street crime and often negatively portrayed in the media (Boomgaarden and Vliegenthart 2007). Both Svensson and Saharso (2014) and (Van der Leun and Van der Woude 2011) argue that this discourse, combined with the emergence of a Dutch version of the culture of control (Garland 2001, van Swaaningen 2005, Pakes 2006), has increased the risk of ethnoracial profiling by the police and other controlling organisations. Recent debates around ethnoracial profiling by the police are also to a large extent centred around the question whether young men with a Moroccan background are disproportionally targeted (Amnesty International 2013).…”
Section: Monitoring Security In An Expanding European Unionmentioning
confidence: 99%
“…Tillyer and Hartley (2010) claim that general negative sentiments in society towards migrant groups can affect the views held by street-level bureaucrats and therefore lead to prejudices informing the decisions they make. In the Netherlands a discourse has developed in which various ethnic minority groups are linked to crime and other social issues (Eijkman 2010, Svensson andSaharso 2014). Especially youngsters with a Moroccan background are seen as disproportionally involved in various forms of street crime and often negatively portrayed in the media (Boomgaarden and Vliegenthart 2007).…”
Section: Monitoring Security In An Expanding European Unionmentioning
confidence: 99%
“…Scholars have not fully investigated whether the police profile immigrants because of their ethnicity (van der Leun & van der Woude, 2011, p. 452). Also, scholars have suggested that the research on ethnic profiling needs to be contemporary (Svensson & Saharso, 2015). Researchers have argued that there has been a substantial shift in the policies targeting ethnic groups within the Netherlands (Downes, 2007; van der Leun & van der Woude, 2011; van der Woude, van der Leun, & Nijland, 2014).…”
Section: Are the Official Police Data Biased Against Ethnic Groups?mentioning
confidence: 99%